Endotoxemia by Porphyromonas gingivalis Alters Endocrine Functions in Brown Adipose Tissue - Hatasa, Masahiro; Ohsugi, Yujin; Katagiri, Sayaka; Yoshida, Sumiko; Niimi, Hiromi; Morita, Kazuki; Tsuchiya, Yosuke; Shimohira, Tsuyoshi; Sasaki, Naoki; Maekawa, Shogo; Shiba, Takahiko; Hirota, Tomomitsu; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Improvement of obesity is important for increasing longevity. The characteristics, size, and function of adipocytes are altered in patients with obesity. Adipose tissue is not only an energy storage but also an endocrine organ. Alteration of endocrine activities in adipose tissue, among them the functional decline of brown adipose tissue (BAT), is associated with obesity. Periodontal disease is a risk factor for systemic diseases since endotoxemia is caused by periodontal bacteria. However, the effect of periodontal disease on obesity remains unclear. Thus, this study aimed to investigate the effect of endotoxemia due to Porphyromonas gingivalis, a prominent cause of periodontal disease, on the BAT. Herein, endotoxemia was induced in 12-week-old C57BL/6J mice through intravenous injection of sonicated 108 CFU of P. gingivalis (Pg) or saline (control [Co]) once. Eighteen hours later, despite no inflammatory M1 macrophage infiltration, inflammation-related genes were upregulated exclusively in the BAT of Pg mice compared with Co mice. Although no marked histological changes were observed in adipose tissues, expressions of genes related to lipolysis, Lipe and Pnpla2 were downregulated after P. gingivalis injection in BAT. Furthermore, expression of Pparg and Adipoq was downregulated only in the BAT but not in the white adipose tissues, along with downregulation of Ucp1 and Cidea expression, which are BAT-specific markers, in Pg mice. Microarray analysis of the BAT showed 106 differentially expressed genes between Pg and Co mice. Gene set enrichment analysis revealed that the cholesterol homeostasis gene set and PI3/Akt/mTOR signaling gene set in BAT were downregulated, whereas the TGF-β signaling gene set was enriched in Pg mice. Overall, intravenous injection of sonicated P. gingivalis altered the endocrine functions of the BAT in mice. This study indicates that endotoxemia by P. gingivalis potentially affects obesity by disrupting BAT function.